PENGARUH LAMA PENYINARAN MATAHARI TERHADAP POTENSI PRODUKSI PADI BERDASARKAN ANALISIS SPASIAL DI KABUPATEN MALANG - Gali Gusira; S Sudarto; Aditya Nugraha Putra (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The agriculture sector holds an essential role to produce foodstuff, including rice. Malang Regency accomplishes about 0,915% from the total of national rice consumption needed. Any natural factor can influence rice productivity such as the time of sun exposure, where sun exposure at around Malang Regency is equal to 7,5-10,7 hour day-1 based on data from 8 climatological stations. This study aimed at analyzing the influence of time exposure toward rice production potential in Malang Regency. The study consisted of four stages, namely: preparation, pre-survey, survey, and data analysis. Data analysis consisted of correlation and stepwise regression tests. The validation test was carried out to test the feasibility of the observed variables. In addition, a spatial analysis was carried out to determine the distribution of the duration of sun exposure and productivity of rice fields in Malang Regency using ArcGIS 10.3. The results showed that the time of exposure gives a low contribution impact on rice production potential with a correlation value of 0.023. This gives an explanation that there is another factor besides the time of sun exposure that could provide a bigger impact. Surface soil permeability in this research is the only other factor that could influence production potential significantly, with influence level as high as 14.7%. But, result from validation test showed that the p-value obtained is equal to 0.000 (p <0.05), indicating a significant difference between potential production based on the exposure with the results of the field survey, so that the exposure factor still could be used to predicted rice production result in Malang Regency.